Pemenuhan Hak Pelayanan Kesehatan Bagi Kelompok Usia Rentan di Indonesia Berdasarkan Asas Keadilan, Kepastian Hukum dan Kemanfaatan - Jaury Douglas Pardomuan; Irwan Triadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Healthcare services for vulnerable age groups are often neglected due to pragmatic considerations. However, in national development, distributive justice and inclusivity must be promoted to help create a society that supports each other and is capable of achieving shared prosperity. This research focuses on a critical analysis of the efforts to fulfill the right to healthcare services for vulnerable age groups, employing a normative-juridical research model with measurement tools based on the principles of justice, legal certainty, and utility. The findings indicate that there is still a lack of detailed and inclusive provisions for vulnerable age groups, which do not yet meet the principles of justice, legal certainty, and utility.